Social Behavior of Social Prone Women Related to Norms, Ethics and Environmental Aesthetics in Prumpung - Darmo Wihardjo, R. Sihadi; Pitri, Fitria; Hasanah, Uswatun; Nurani, Yuliani; Ramadhan, Syahrul (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to describe how people’s views and social behavior of Socially Prone Women (SPW) are related to norms, ethics, and environmental aesthetics. This research was conducted using a qualitative approach. The subjects used in this study were four SPW families consisting of children who went to school and did not attend school as well as mothers who worked as SPW, residents who live in the Prumpung, the head of the local neighborhood, and one elder who lived long in the Prumpung area. The data collected by conducting in-depth interviews with informants. Besides, researchers also made observations about the SPW family’s daily life in the Prumpung. Although it has been written, the norms that have been made and agreed by the residents and the local neighborhood head remain ignored. It could be seen from the ethics that reflected or shown to the local community. Not a few of them show bad ethics such as using disrespectful clothes, littering and not obeying the rules made by the local neighborhood. Therefore, the neglected norms through ethics could lead to the destruction of the environment.